Vejrforholdene i Landbrugsaaret 1946-47. (Fra 1. Oktober 1946 til 30. September 1947.) - Hansen, H. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i Landbrugsaaret 1946-47. (Fra 1. Oktober 1946 til 30. September 1947.)